Of Bachelors’ of computer engineering training according to the industry standards of higher education in Ukraine (Pedagogy of Higher and Secondary Education, 2015)
Sorokopud M. A. of Bachelors’ of computer engineering training according to the industry standards of higher education in Ukraine.The article considers the main approaches to the Bachelors’ of computer engineering training in Ukraine. The analysis of the professional competences of the future specialists wascarried out. A general study time sharing by cycles of training and hours sharing by disciplines of mathematics and natural science was considered. The role of Physics during the process of future specialists training was emphasized.
Keywords: bachelors; computer engineering; Bachelors’ training; industry standard; Physics